Efektivitas Operasional dan Tantangan Pengelolaan Koperasi Ritel: Studi Kasus Koperasi Mart pada Koperasi Konsumen Pejuang Empat Lima - Rangga Oncar Dharmesta; Achmad Daengs GS; Robbi Rachim (Jurnal Pengabdian Masyarakat, 2025)
This research aims to examine the operational mechanisms and identify managerial issues within the Cooperative Mart unit under the Consumer Cooperative Pejuang Empat Lima. Employing a qualitative case study approach, data were obtained through direct observation, in-depth interviews with managers and administrators, and analysis of internal documents conducted during an internship from April 8 to May 8, 2025. The results reveal that Koperasi Mart operates using a hybrid system that combines manual and digital methods for transaction recording and inventory control. The cooperative not only functions as a retail provider of daily necessities but also as a practical embodiment of cooperative values among its members. Despite its potential, the organization encounters several management obstacles, including the absence of a clear leadership transition process, inconsistencies in operational procedures, and limited supervision. To enhance efficiency, this study suggests appointing a permanent operational leader, establishing structured work schedules, and improving documentation practices to ensure sustainable and organized management of Koperasi Mart’s business operations.